SWAZI VOCAL MUSIC. David Rycroft. No. 1 of Series of African Music Musee Royal de l'Afrique Centrale, Tervuren and the Belgishe Radio en Televisie. (International Library of African Music, 1969)
The advent of a series of this nature is warmly to be welcomed. The selection of Swazi songs is as representative as possible of the styles of Swazi singing collected by an expert in the Nguni languages.
Keywords: African Music